KEEFEKTIVITASAN PENCAIRAN DANA BEASISWA KIP-K YANG DIBERIKAN PEMERINTAH KEPADA PARA MAHASISWA - Tamaulina Br Sembiring,; Laura Engellina Br Sianturi,; Mutia Salsabila,; Bagus Riandi,; Luthfi Alghifari Batubara,; Sikapta Ari Gurusinga, (Journal of Innovation Research and Knowledge, 2025)
This study examines the effectiveness of government policies, especially the Ministry of Education and Culture and Research, in distributing the Indonesia Smart Card (KIP) Lecture scholarship funds to recipient students. KIP Kuliah is regulated in Law No. 12/2012 on Higher Education and strengthened by Presidential Regulation No. 62/2021, which emphasizes the state's commitment to ensuring access to higher education for underprivileged students. However, the implementation of this policy still faces various obstacles, especially the delay in disbursement of funds which has an impact on the administration of tuition payments at universities. This study uses a normative juridical research method, which highlights the factors that cause delays, such as complicated bureaucracy, unclear information, slow campus administration processes, and student non-compliance with channeling bank rules. In addition, the wide scope of recipients and the long data collection mechanism also slowed down the disbursement process. The results show that the effectiveness of the KIP Lecture fund distribution policy is strongly influenced by the synergy between the government, universities, and students in complying with established procedures. Improving bureaucracy, increasing coordination, and educating students are the keys to optimally achieving the objectives of the KIP Lecture program